A Feasibility Study for the Hot-Air-Assisted Reflow Soldering Process Based on Computational Fluid Dynamics - Natcha Kanjad; Chanapat Chanbandit; Jatuporn Thongsri (My University, 2024)
In hard disk drive (HDD) manufacturing, a reflow soldering process (RSP) employs heat generated at the welding tip (WT) to bond tiny electrical components for assembling an HDD. Generally, the heat was generated by an electric current applied to the WT. This article reports a feasibility study of using hot air based on computational fluid dynamics (CFD), a choice to assist heat generation. First, the WT and hot air tube (HAT) prototypes were designed and created. The HAT is a device that helps to supply hot air directly to generate heat at the WT. Then, the experiment was established to measure the temperature (T) supplied by the hot air. The measure results were employed to validate the CFD results. Next, the prototype HAT was used to investigate the T generated at the WT by CFD. The comparison revealed that the T measured by the experiment was in the 106.2 °C–133.5 °C range and that the CFD was in the 107.3 °C–136.6 °C range. The maximum error of the CFD results is 2.3% compared to the experimental results, confirming the credibility of the CFD results and methodology. The CFD results revealed that the operating conditions, such as WT, HAT designs, hot air inlet velocity, and inlet temperature, influence the T. Last, examples of suitable operating conditions for using hot air were presented, which confirmed that hot air is a proper choice for a low-temperature RPS.
Keywords: Reflow soldering; Fluid Dynamics and Heat Transfer